2013
DOI: 10.1186/1479-5876-11-275
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of miR-138 promotes colorectal cancer metastasis via directly targeting TWIST2

Abstract: BackgroundColorectal cancer (CRC) is the most common digestive system malignancy. The molecular events involved in the development and progression of CRC remain unclear. Recently, more and more evidences have showed that deregulated miRNAs participate in colorectal carcinogenesis.MethodsThe expression levels of miR-138 were first examined in CRC cell lines and tumor tissues by real-time PCR. The in vitro and in vivo functional effects of miR-138 were examined further. Luciferase reporter assays were conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 27 publications
2
56
1
Order By: Relevance
“…Downregulation of miR-138 has been identified in several cancer types, including breast cancer (21), bladder cancer (22), larynx carcinoma (23), colorectal cancer (24,25), non-small cell lung cancer (26,27), oral squamous cell carcinoma (28), gallbladder carcinoma (29), pancreatic cancer (30), hepatocellular carcinoma (31) and glioblastoma (32). More significantly, miR-138 expression levels were observed to be correlated with clinicopathological features of cancer patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Downregulation of miR-138 has been identified in several cancer types, including breast cancer (21), bladder cancer (22), larynx carcinoma (23), colorectal cancer (24,25), non-small cell lung cancer (26,27), oral squamous cell carcinoma (28), gallbladder carcinoma (29), pancreatic cancer (30), hepatocellular carcinoma (31) and glioblastoma (32). More significantly, miR-138 expression levels were observed to be correlated with clinicopathological features of cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Sun et al noted that miR-138 targeted zinc finger E-box-binding homeobox 2 to suppress bladder cancer invasion and metastases (22). Long et al demonstrated that inhibition of miR-138 in colorectal cancer cells resulted in a significant reduction of migration and invasion capacity by directly targeting TWIST2 (25). In non-small cell lung cancer, miR-138 decreased cell proliferation, migration in vitro and tumor growth in vivo, and increased cisplatin sensitivity through targeting multiple genes, including G protein-coupled receptor kinase interacting ArfGAP 1 (GIT1), semaphorin 4C, cyclin D3, Glucose regulated protein 124 (GRP124), enhancer of zeste homolog 2 and pyruvate dehydrogenase kinase 1 (26,(33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al (35) revealed that miR-138 overexpression suppressed oral squamous cell carcinoma (36) and gallbladder carcinoma cell growth. Yang et al (26) found that miR-138 expression resulted in a significant inhibition of colorectal cancer cell migration and invasion in vitro and in vivo. In ovarian cancer, miR-138 overexpression repressed cancer cell invasion and metastasis (24).…”
Section: Discussionmentioning
confidence: 99%
“…miR-138, a family of microRNA precursors, has been reported to function as a tumor suppressor in a variety of human cancers, including renal carcinoma (13), non-small lung cancer (14), colorectal cancer (15), neuroblastoma (16), esophageal squamous cell carcinoma (17), nasopharyngeal carcinoma (18) and hepatocellular carcinoma (19). However, the role and the molecular mechanisms of miR-138 in cervical remain unclear.…”
Section: Introductionmentioning
confidence: 99%